Omega-3 PUFAs and gut microbiota: A preventive approach for colorectal cancer - Marco Giammanco (PAGEPress Publications, 2021)
The influence of diet on the composition of the intestinal microbiota and related pathologies has been known for some time. Some classes of nutrients, such as fatty acids belonging to the omega 3 series, have particular effects on the bacteria that make up the intestinal microbiota. ω-3 PUFAs affect the gut microbiota in three different ways: by modulating the type and abundance of intestinal bacteria, by regulate SCFAs levels, and by alter the levels of proinflammatory mediators. Through these modalities, ω-3 PUFAs could be useful for the prevention of intestinal diseases such as colorectal cancer (CRC). The ability of ω-3 PUFAs to modulate the intestinal inflammatory response, to preserve the integrity of the intestinal mucosa and to modulate the bacterial composition of the intestine, could be useful as a preventive strategic approach to hinder the development of CRC.